NANOEMULSÕES CONTENDO EXTRATO HIDROALCOÓLICO DE AÇAÍ (Euterpe oleracea Mart.) PARA NORMALIZAÇÃO DA INFLAMAÇÃO CRÔNICA ASSOCIADA A DOENÇAS NEUROPSIQUIÁTRICAS - Souza, Diulie Valente de (2020)
The pathophysiology of neuropsychiatric diseases such as schizophrenia, bipolar mood disorder, and depression are not completely understood, being recently associated with mitochondrial dysfunction and oxidative stress, and a consequent exaggerated inflammatory response. For the treatment of such pathologies, potent drugs are used, responsible for many side effects due to the use of high dosages for a prolonged time. In view of this, numerous studies have been developed in the search for new therapeutic alternatives, especially involving the use of natural products. Euterpe oleracea Mart. popularly known as açaí, it is a fruit native to the Amazon region that has proven to have a neuroprotective effect. However, there are still no scientific studies that demonstrate the anti-neuroinflammatory effect of such a natural product. In addition, it is known that the stability of this extract in relation to time and oxidation by environmental exposure can compromise its effectiveness. For this purpose, a hydroalcoholic extract of açaí was initially produced and characterized. Then, treatments were performed based on a concentration-response curve of the extract in cells of the BV-2 lineage to evaluate the effect of the extract, afterwards the cells were activated by exposure to lipopolysaccharide (inflammation induction model) for verification the anti-inflammatory effect of the same. Then a nanoemulsion was produced using the spontaneous emulsification method in order to assist in the protection of its bioactives and also to evaluate the anti-inflammatory effect of this structure. The nanoemulsion was characterized in terms of size, polydispersity index, zeta potential and pH. The stability of the formulation for 30 days in different storage conditions was also evaluated. The nanoemulsions had droplet size with diameter on a nanoscale, low polydispersity index, negative zeta potential, basic pH, with storage under refrigeration being the best storage condition. Regarding the evaluation of açaí nanoemulsion in the BV-2 strain, no significant damage was observed. Regarding the anti-inflammatory effect, it was observed that the nanoformulation was able to reduce cell reactivity, not at levels of proliferation equal to the negative control, but in comparison to the positive control (LPS) and a normalization of the oxidative profile. The açaí extract has already proven anti-inflammatory activity, however it is suggested that nanoformulation can act in order to potentiate such action, and can even cross the blood brain barrier and modulate the chronic inflammation associated with neuropsychiatric diseases.